INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER PADA PESERTA DIDIK DI SD INPRES 2 WAGOM - Alhamid, Ipa Salma; Nur, Indria; Hasbullah (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
This research aims to plan the process of internalizing Islamic education values ​​in character building for students at Inpraes 2 Wagon Elementary School, implementing the process of internalizing Islamic education values ​​in character building for students at Inpres 2 Wagom Elementary School, evaluating the process of internalizing Islamic education values ​​in character building. in Inpres 2 Wagom Elementary School students. This research uses a descriptive qualitative method, a data mining method using interview methods, hearing aids, cameras and observation phones. Documentation. Primary data sources are the school principal and teacher. Data analysis methods use, Data Reduction (Data Redukcion), data presentation (Data Display), Data verification (Conduction/Drawing). The internalization of Islamic education values ​​in character formation at SD Inpres 2 Wagom is carried out by referring to the principle that students are assessed by looking at the extent of their understanding, appreciation and practice of students' behavior.